Pandangan Islam Tentang Riba Dalam Transaksi Keuangan: Tinjauan Ayat Al-Qur’an, Hadis, dan Pendapat Para Ulama - Rozatul Ikhwa; Rayyan Firdaus (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
Various economic systems, including Islamic ones, have debated usury in financial transactions. Because it is considered detrimental to one of the parties and contrary to the principles of justice, usury, which literally means unfair additions or profits in transactions, is prohibited in Islam. By referring to primary sources such as the Qur'an and Hadith, as well as the opinions of fiqh scholars, this research aims to study the Islamic perspective on the use of riba in recording financial transactions. Understanding the use of usury in recording financial transactions is the main objective of this research. The research results show that Islam emphasizes the prohibition of usury in recording financial transactions and encourages the use of a financial system that is based on the principles of balance, transparency and mutual benefit. Apart from that, this research also discusses alternative efforts that can be used by the Islamic financial system to replace the practice of usury, such as the application of fairer principles for results (mudharabah) and buying and selling (murabahah). Thus, the Islamic financial system can stop the practice of usury.